Facile Oxidation of Alcohols to Aldehydes or Ketones with 1-Acetoxy-5-nitro-1,2-benziodoxole-3(1H)-one - Iinuma, Masataka; Moriyama, Katsuhiko; Togo, Hideo (Synlett, 2013)
Various benzylic alcohols and aliphatic secondary alcohols were smoothly oxidized to the corresponding aromatic aldehydes, aromatic ketones, and aliphatic ketones, respectively, with the novel 1-acetoxy-5-nitro-1,2-benziodoxole-3(1H)-one (ANBX) alone, a trivalent iodine prepared from the oxidation of 2-iodo-5-nitrobenzoic acid with MCPBA. The present reaction is the first effective method for the oxidation of alcohols with a trivalent iodine alone under mild reaction conditions.
Keywords: 1-acetoxy-5-nitro-1,2-benziodoxole-3(1H)-one; oxidation; alcohol; aldehyde; ketone